Dissection of a grain yield QTL from wild emmer wheat reveals sub-intervals associated with culm length and kernel number - Deblieck, Mathieu; Szilagyi, Gergely; Andrii, Fatiukha; Saranga, Yehoshua; Lauterberg, Madita; Neumann, Kerstin; Krugman, Tamar; Perovic, Dragan; Pillen, Klaus; Ordon, Frank (Frontiers in Genetics, 2022)
Genetic diversity in wheat has been depleted due to domestication and modern breeding. Wild relatives are a valuable source for improving drought tolerance in domesticated wheat. A QTL region on chromosome 2BS of wild emmer wheat (Triticum turgidum ssp. dicoccoides), conferring high grain yield under well-watered and water-limited conditions, was transferred to the elite durum wheat cultivar Uzan (T. turgidum ssp. durum) by a marker-assisted backcross breeding approach. The 2B introgression line turned out to be higher yielding but also exhibited negative traits that likely result from trans-, cis-, or linkage drag effects from the wild emmer parent. In this study, the respective 2BS QTL was subjected to fine-mapping, and a set of 17 homozygote recombinants were phenotyped at BC4F5 generation under water-limited and well-watered conditions at an experimental farm in Israel and at a high-throughput phenotyping platform (LemnaTec-129) in Germany. In general, both experimental setups allowed the identification of sub-QTL intervals related to culm length, kernel number, thousand kernel weight, and harvest index. Sub-QTLs for kernel number and harvest index were detected specifically under either drought stress or well-watered conditions, while QTLs for culm length and thousand-kernel weight were detected in both conditions. Although no direct QTL for grain yield was identified, plants with the sub-QTL for kernel number showed a higher grain yield than the recurrent durum cultivar Uzan under well-watered and mild drought stress conditions. We, therefore, suggest that this sub-QTL might be of interest for future breeding purposes.